2018
DOI: 10.1021/acs.jpca.8b04590
|View full text |Cite
|
Sign up to set email alerts
|

Control of Interfacial Cl2 and N2O5 Reactivity by a Zwitterionic Phospholipid in Comparison with Ionic and Uncharged Surfactants

Abstract: Gas-liquid scattering experiments reveal that charge-separated but neutral (zwitterionic) surfactants catalyze the oxidation of dissolved Br to Br by gaseous Cl at the surface of a 0.3 M NaBr/glycerol solution. Solutions of NaBr dissolved in glycerol with no surfactant were compared with solutions coated with zwitterionic, cationic, and anionic surfactants at dilute surface concentrations of 1.1 to 1.5 × 10 cm (less than 65% of maximum chain packing). The zwitterionic phospholipid enhances Cl conversion of Br … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 95 publications
2
24
1
Order By: Relevance
“…The presence of a strongly surface-active anion could displace Cl – in the near-surface region, leading to a suppression in Φ ClNO 2 . The opposite effect has recently been suggested for cationic surfactants: an increase in N 2 O 5 reactivity in the presence of cationic surfactants was attributed to an enhancement in the near-surface concentration of halide ions . In the case of sodium acetate, we observe a slight increase in the surface tension of a 0.5 M NaCl/D 2 O solution upon addition of 1.0 M NaAc (Figure ), suggesting that the carboxylate group does not preferentially accumulate near the surface.…”
Section: Results and Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…The presence of a strongly surface-active anion could displace Cl – in the near-surface region, leading to a suppression in Φ ClNO 2 . The opposite effect has recently been suggested for cationic surfactants: an increase in N 2 O 5 reactivity in the presence of cationic surfactants was attributed to an enhancement in the near-surface concentration of halide ions . In the case of sodium acetate, we observe a slight increase in the surface tension of a 0.5 M NaCl/D 2 O solution upon addition of 1.0 M NaAc (Figure ), suggesting that the carboxylate group does not preferentially accumulate near the surface.…”
Section: Results and Discussioncontrasting
confidence: 41%
“…The opposite effect has recently been suggested for cationic surfactants: an increase in N 2 O 5 reactivity in the presence of cationic surfactants was attributed to an enhancement in the near-surface concentration of halide ions. 28 In the case of sodium acetate, we observe a slight increase in the surface tension of a 0.5 M NaCl/D 2 O solution upon addition of 1.0 M NaAc (Figure 3), suggesting that the carboxylate group does not preferentially accumulate near the surface. As expected in the case of a salt containing a doubly charged ion, the surface tension of Na 2 SO 4 solutions also increases with increasing sulfate concentration.…”
Section: Methodsmentioning
confidence: 89%
“…16 However, recent work has shown that surfactant coatings on SSA can actually enhance certain reactions. 17 Laboratory studies with ambient seawater also show suppression of SSA hygroscopicity by certain organics, potentially altering cloud condensation nuclei (CCN) activity. 18,19 Enhanced cloud ice nucleation efficiency is observed for Arctic seawater, suggesting a contribution of SSA to cloud ice formation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Submicron SSA particles (<1 μm; ∼200 nm number mode) can be significantly enriched in organic matter (>50%, by mass) in comparison to bulk seawater. , SSA organic coatings can inhibit heterogeneous reactions of trace gases, inhibiting particulate chloride depletion, and impacting trace gas budgets and atmospheric composition . However, recent work has shown that surfactant coatings on SSA can actually enhance certain reactions . Laboratory studies with ambient seawater also show suppression of SSA hygroscopicity by certain organics, potentially altering cloud condensation nuclei (CCN) activity. , Enhanced cloud ice nucleation efficiency is observed for Arctic seawater, suggesting a contribution of SSA to cloud ice formation. Despite important climate implications for cloud formation and phase, and associated longwave radiative forcing, limited knowledge exists regarding ambient SSA organic coatings and the transfer of marine biogenic organics to the particle phase, particularly for Arctic winter.…”
Section: Introductionmentioning
confidence: 99%
“…The lipid monolayer interface has largely been studied for its biological relevancemonolayers occur in the body as lung surfactants and tear filmsbut is also of great interest to the atmospheric chemistry community for its role in modulating sea spray aerosol (SSA) particle reactions and dynamics. Lipid monolayers are known to coat the ocean surface and the surface of nascent SSA and can significantly impact SSA climate-relevant properties. , It has been shown that the lipid type and composition of SSA surfaces have all been found to influence hygroscopicity, , cloud condensation nucleation activity, ,, and ice nucleation activity of SSA. , Amphiphilic lipids can impact interfacial properties of SSA primarily because they are surface-active. Surfactants such as phospholipids participate in photooxidation and ozonolysis, their anionic headgroups selectively bind and concentrate trace metal cations at the surface, and their carbon chain length and headgroup charge(s) influence the transport and reactivity of gases at the interface. While the chemical composition of SSA and their effects on climate are becoming more resolved, the molecular structure and dynamics of SSA surfaces remain difficult to probe experimentally. Computational methods such as all-atom molecular dynamics (MD) have therefore contributed largely to the existing body of work on the lipid monolayer interface. Since computational methods can resolve chemical systems at the atomic level, the integration of computation with experimental aerosol techniques is expected to significantly advance our ability to model the SSA interface . The present study thus takes an integrated computational and experimental approach to understand how the lipid monolayer surface of SSA is affected by the presence of lipase.…”
Section: Introductionmentioning
confidence: 99%